2014
DOI: 10.1103/physrevlett.113.200404
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Orbital Angular Momentum States with Chiral Polaritonic Lenses

Abstract: Controlled transfer of orbital angular momentum to an exciton-polariton Bose-Einstein condensate spontaneously created under incoherent, off resonant excitation conditions is a long-standing challenge in the field of microcavity polaritonics. We demonstrate, experimentally and theoretically, a simple and efficient approach to the generation of nontrivial orbital angular momentum states by using optically induced potentials-chiral polaritonic lenses. These lenses are produced by a structured optical pump with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 46 publications
3
100
1
Order By: Relevance
“…Polaritons form a quantum fluid, and prominent examples of observed phenomena include parametric amplification [18] and Bose condensation ( [19,20] and references therein). Polaritonic quantum fluids can support vortices [21,22], and it was recently demonstrated that OAM can be transferred to polaritonic Bose-Einstein condensates using chiral polaritonic lenses [23], and that the number of vortices can be controlled by controlling the OAM of the pump beams [24,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polaritons form a quantum fluid, and prominent examples of observed phenomena include parametric amplification [18] and Bose condensation ( [19,20] and references therein). Polaritonic quantum fluids can support vortices [21,22], and it was recently demonstrated that OAM can be transferred to polaritonic Bose-Einstein condensates using chiral polaritonic lenses [23], and that the number of vortices can be controlled by controlling the OAM of the pump beams [24,25].…”
mentioning
confidence: 99%
“…Polaritons form a quantum fluid, and prominent examples of observed phenomena include parametric amplification [18] and Bose condensation ([19,20] and references therein). Polaritonic quantum fluids can support vortices [21,22], and it was recently demonstrated that OAM can be transferred to polaritonic Bose-Einstein condensates using chiral polaritonic lenses [23], and that the number of vortices can be controlled by controlling the OAM of the pump beams [24,25].The question remains whether the relatively strong interaction between polaritons can be used to manipulate, in a well-controlled fashion, the orbital and/or spin angular momentum of polaritons (and thus the light field emitted from the cavity). For example, is it possible to use a beam with OAM of m p and create additional OAM contributions, say two components of OAM m 1 and m 2 , and to use the light beam characteristics of frequency and intensity to control m 1 and m 2 ?…”
mentioning
confidence: 99%
“…[104,105]. However the principal feature of lasing by the array of dielectric spheres is that the laser beam carries the OAM without use of special chiral symmetry broken media [86,90,91].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For different types of chiral polaritonic lenses, it was shown that the near-field chirality can lead to the tailoring optical OAM in the far-field region [86,87]. There were many proposals to generate OAM beams by use of chiral plasmonic nanostructures [86], ferrite particles [88], the monolithic integration of spiral phase plates [89], chiral polaritonic lenzes [90], and by designer metasurfaces [91], etc.…”
Section: Transfer Of Sam Into Oam Of the Bsc With M =mentioning
confidence: 99%
“…Chiral trapping potentials can also be engineered to generate vortices [49]. Experiments with Mexican hat shaped profiles showed how it was possible to trap vortex-antivortex pairs [50].…”
Section: Trapping and Condensation In Structured Potentialsmentioning
confidence: 99%